2010
DOI: 10.1074/jbc.m110.146209
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Dynamics of the Bovine Mitochondrial ADP/ATP Carrier Isoform 1 Revealed by Hydrogen/Deuterium Exchange Coupled to Mass Spectrometry

Abstract: The mitochondrial adenine nucleotide carrier (Ancp) catalyzes the transport of ADP and ATP across the mitochondrial inner membrane, thus playing an essential role in cellular energy metabolism. During the transport mechanism the carrier switches between two different conformations that can be blocked by two toxins: carboxyatractyloside (CATR) and bongkrekic acid. Therefore, our understanding of the nucleotide transport mechanism can be improved by analyzing structural differences of the individual inhibited st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
65
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 45 publications
10
65
3
Order By: Relevance
“…Pro-247 is located in the C-terminal part of TMH5, which displays the Ancp signature sequence, RRRMMM. This region of BfAnc1p exhibited similar accessibility to the solvent whatever the inhibitor bound (14), suggesting TMH5 is less flexible than its counterparts TMH1 and -3. This is in accordance with our results and with molecular dynamics experiments during which, movements around the prolyl residue in TMH5 are less important than movements around the prolyl residue in TMH1 (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pro-247 is located in the C-terminal part of TMH5, which displays the Ancp signature sequence, RRRMMM. This region of BfAnc1p exhibited similar accessibility to the solvent whatever the inhibitor bound (14), suggesting TMH5 is less flexible than its counterparts TMH1 and -3. This is in accordance with our results and with molecular dynamics experiments during which, movements around the prolyl residue in TMH5 are less important than movements around the prolyl residue in TMH1 (13).…”
Section: Discussionmentioning
confidence: 99%
“…This reorganization unlocks the three odd-numbered TMH allowing the protein to expand in the matrix half. Besides, deuterium exchange experiments carried out with the BfAnc1p showed that TMH1, -2, -3, and -5 were much less exposed to the solvent on the IMS side in the BA complex than in the CATR complex, indicating rearrangement of the two halves of the carrier: the one oriented through the matrix and the other one to the IMS, one relative to the other (14). Similar experiments carried out with yeast ScAnc2p evidenced inhibitor-dependent deuterium accessibility: the matrix loops were more deuterated in the presence of BA than in the presence of CATR (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria were transformed according to standard methods using CaCl 2 (11 (14), and JL1-3ANC2⌬por1 (W303-1B anc1::LEU2 anc3:: URA3 por1::HIS3). 6 Strains were cultivated and transformed as described (15). A full description of the compositions of all media used, YPL (lactate-containing rich medium) and YNB Glc W Ϫ and YNB Gal W Ϫ (tryptophan-free minimal medium containing glucose or galactose, respectively) can be found in Clémençon et al (15).…”
Section: Chemicals and Immunochemicals-ba And [mentioning
confidence: 99%
“…Recently, both complexes were compared in detergent solution by hydrogen/deuterium exchange coupled to mass spectrometry (HDX-MS). These analyses provided new information on the BA conformation and, thus, on the conformational dynamics of bAnc1p during ADP/ATP transport (6). However, the bovine model remains limited to biochemical studies of the native form because its overexpression in bacteria or in yeast is difficult (7).…”
mentioning
confidence: 99%